2007
DOI: 10.1002/bit.21430
|View full text |Cite
|
Sign up to set email alerts
|

A scaffold for the Chinese hamster genome

Abstract: Chinese hamster ovary (CHO) cells are a prevalent tool in biological research and are among the most widely used host cell lines for production of recombinant therapeutic proteins. While research in other organisms has been revolutionized through the development of DNA sequence-based tools, the lack of comparable genomic resources for the Chinese hamster has impeded similar work in CHO cell lines. A comparative genomics approach, based upon the completely sequenced mouse genome, can facilitate genomic work in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Unassigned scaffolds and scaffolds assigned to the unseparated hamster chromosome 9 and 10 library were instead mapped to the mouse genome. Scaffolds that could be aligned uniquely were assigned to a hamster chromosome based on published hamster chromosome localization [Yang et al, 2000], [Wlaschin and Hu, 2007]. Fifteen scaffolds (18.79 Mb) could be assigned to chromosome 9 and 2 scaffolds (32.58 Mb) to chromosome 10.…”
Section: Resultsmentioning
confidence: 99%
“…Unassigned scaffolds and scaffolds assigned to the unseparated hamster chromosome 9 and 10 library were instead mapped to the mouse genome. Scaffolds that could be aligned uniquely were assigned to a hamster chromosome based on published hamster chromosome localization [Yang et al, 2000], [Wlaschin and Hu, 2007]. Fifteen scaffolds (18.79 Mb) could be assigned to chromosome 9 and 2 scaffolds (32.58 Mb) to chromosome 10.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we could have two distinct situations: either a functional coupling between the CFTR protein and an endogenous aquaporin, or a cAMP-stimulated aqueous pore within the CFTR protein. Quantitative information concerning the expression of endogenous proteins by CHO cells is scarce (Wlaschin and Hu, 2007). However, we have focussed our study on two aquaporins, AQP3 and AQP9, because it has been shown they are both cAMP-dependent 'aquaglycoporins', indirectly and positively activated by the CFTR protein (Schreiber et al, 1999;Pietrement et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Harvested cells (2 Â 10 6 cells) were centrifuged and the total RNA was extracted from the cell pellets using the RNeasy Kit (Qiagen GmbH, Hilden, Germany) according to manufacturer's protocol. Ten micrograms of the extracted biotin labeled cRNA was hybridized on a custom-made CHO-specific Affymetrix microarray (Yee et al, 2008b) containing 10,118 probe sets with 7,525 unique sequences that represent a subset from a collection of 16,136 unique CHO cell and Chinese hamster transcripts obtained by comprehensive EST sequencing as described by Wlaschin et al (2005) and Wlaschin and Hu (2007). Samples were scanned in highresolution mode and data were processed with an Affymetrix GeneChip Scanner 3000 system (Affymetrix, Inc., Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%